2004
DOI: 10.1177/1534582304270783
|View full text |Cite
|
Sign up to set email alerts
|

A Central Role for Norepinephrine in the Modulation of Cerebellar Learning Tasks

Abstract: Norepinephrine (NE) is a central nervous system neuromodulator that enhances the actions of other neurotransmitters such as gamma-aminobutyric acid and glutamate. Based on the Marr-Albus theories, Gilbert suggested that NE influences consolidation of cerebellar learning. NE depletion or blockade of postsynaptic noradrenergic receptors decreases the rate of learning in several cerebellar-dependent learning tasks. Loss of cerebellar beta-adrenergic receptor function correlates with a loss of function in related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 86 publications
(102 reference statements)
2
12
0
Order By: Relevance
“…Homologous recombination techniques have shown that complete removal of either the enzymes responsible for noradrenaline metabolism or the vesicular monoamine transporter has deleterious consequences for foetal survival [37]. Moreover, blockade of postsynaptic noradrenergic receptors decreases the rate of learning in several cerebellar-dependent motor tasks [38]. The possibility of integrating and complementing noradrenergic with purinergic mechanisms to increase the strength of synaptic connections through activation of both noradrenergic and P2Y 1 receptors might therefore constitute also a novel powerful approach against neuronal degeneration and/or malfunctioning in the cerebellum.…”
Section: Discussionmentioning
confidence: 99%
“…Homologous recombination techniques have shown that complete removal of either the enzymes responsible for noradrenaline metabolism or the vesicular monoamine transporter has deleterious consequences for foetal survival [37]. Moreover, blockade of postsynaptic noradrenergic receptors decreases the rate of learning in several cerebellar-dependent motor tasks [38]. The possibility of integrating and complementing noradrenergic with purinergic mechanisms to increase the strength of synaptic connections through activation of both noradrenergic and P2Y 1 receptors might therefore constitute also a novel powerful approach against neuronal degeneration and/or malfunctioning in the cerebellum.…”
Section: Discussionmentioning
confidence: 99%
“…In the neocortex and cerebellum mRNA transcript levels of bdnf and narp are higher when measured after wakefulness (relative to sleep). Learning and plasticity in the neocortex and cerebellum, are also both strongly influenced by NA [72, 73]. Learning and plasticity in the cerebellum, however, appear to be governed by LTD, and to a lesser extent, forms of LTP that are quite distinct from those observed in the neocortex [21].…”
Section: The Theory Of Shy Re-examinedmentioning
confidence: 99%
“…Emotional arousal activates locus coeruleus neurons, and the released norepinephrine modulates synaptic plasticity in various brain regions and is implicated in memory formation, consolidation and retrieval 16, 17 . It has also been proposed that norepinephrine plays a role in modulation of cerebellum-dependent learning 18, 19 , and injection of β-adrenergic antagonist into the rabbit flocculus diminishes the gain-up adaptation of VOR 20, 21 . However, it is not known whether the β-adrenergic receptor contributes to the gain increase adaptation of OKR induced by various training paradigms.…”
Section: Introductionmentioning
confidence: 99%